The Narrative of Crime in Andrea Hirata's Novel 'Orang-Orang Biasa': A Formulaic Study - Sari, Hanifah Yulia; Rachman, Aditya; Putri, Diantri Seprina; Ulya, Ridha Hasnul; Widhyah, Dhini Yustia (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2024)
The topic of criminality is often viewed as a literary genre closely associated with themes of crime, heroes and anti-heroes, mysterious plots, suspense, plot twists, and violent scenes. This study employs Andrea Hirata's novel "Orang-orang Biasa" as its material object. The data consists of text content in words, phrases, and sentences that align with the predetermined scholarly inquiry. This research uses John G. Cawelti's theoretical framework to delineate data that reveal patterns in narrative structure and character development, thereby classifying the novel as belonging to the crime genre. The findings of this study indicate that the criminal formula presented by Andrea Hirata in "Orang-orang Biasa" is a type of criminal comedy. The results of this study reveal that the formula similarities between Orang-orang Biasaand literary works in the crime genre can be observed in the story motives, setting choices, the presence of additional events accompanying the main narrative, and the characters. The author's presentation of these formulas indicates that the novel belongs to the comedy-crime genre